2013
DOI: 10.1016/j.jegh.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequity in health care utilization, Iran

Abstract: People with higher HEI used more specialist and GP care, while people with lower HEI used more HW care. The inequity in HCU was low and non-significant in different quintiles of males, females, urban and rural, as well as those who were insured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 22 publications
3
39
0
Order By: Relevance
“…The Iranian government subsidizes FP program in the rural areas and cities with less than 20000 population and all primary health services are free. Our findings are consistent with of the results of a study in Markazi province in Iran (29). Other international studies in Australia, Korea, and Northern Sweden (16,19,20) show that in developed countries with universal health coverage, where the government subsidizes primary health services, all services represent a pro-poor pattern.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The Iranian government subsidizes FP program in the rural areas and cities with less than 20000 population and all primary health services are free. Our findings are consistent with of the results of a study in Markazi province in Iran (29). Other international studies in Australia, Korea, and Northern Sweden (16,19,20) show that in developed countries with universal health coverage, where the government subsidizes primary health services, all services represent a pro-poor pattern.…”
Section: Discussionsupporting
confidence: 92%
“…A few studies have examined health care utilization inequity in Iran (22)(23)(24)(25)(26), most of which have measured health inequalities in different health care services (27)(28)(29)(30)(31). Most of these studies have evaluated subnational data, therefore, their data cannot be used at the national level (25,26,32).…”
mentioning
confidence: 99%
“…Research that has been done in India found that the highest decay prevalence has been found on children who lived at orphanage, with the average of teeth that have to be treated is 1 tooth 26.2%, 2 teeth or more 12.3%, 11.1% need tooth extraction, 19% need endodontic treatment, and 0.9% need fissure sealant treatment [19]. From the results of research in some countries, access to oral and dental care on a regular basis in the past year as in Jordan, 47.4%; in India 46% [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…[ 4 5 6 7 8 9 ] People with a higher socioeconomic status use health care more than people from the lower-income groups, as also, specialist care is most used by rich people. [ 10 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of our recent studies and other literature, the educational level is an important predictor of healthy life and can also affect health care utilization. [ 11 15 16 17 ] Moreover, educational attainment is the greatest predictor of Socioeconomic Status (SES)[ 3 ] and it is common that inequity has been measured based on the different levels of socioeconomic status, but different studies have shown that there is an evidence of inequity in the different levels of education. [ 15 17 18 ] Therefore, the current study aims to determine the inequity in OHC with regard to the educational level of parents of six- to seven-year-old children in the Qom province of Iran.…”
Section: Introductionmentioning
confidence: 99%